Un enfoque relax and cut usando una formulación de flujo multiproductos para el problema del agente viajero - Kawashima, Makswell Seyiti [UNESP]; Rangel, Socorro [UNESP]; Litvinchev, Igor; Infante, Luis (Universidad Nacional de Colombia, 2015)
In this paper we explore the multi-commodity flow formulation for the Asymmetric Traveling Salesman Problem (ATSP) to obtain dual bounds. The procedure employed is a variant of a relax and cut procedure proposed in the literature that computes the Lagrangean multipliers associated to the subtour elimination constraints preserving the optimality of the multipliers associated to the assignment constraints. The results obtained by the computational study are encouraging and show that the proposed algorithm generated good dual bounds for the ATSP with a low execution time.
A relax and cut approach using the multi-commodity flow formulation for the traveling salesman problem
Keywords: Lagrangean relaxation; Relax and cut; Traveling salesman problem